Electron correlation effects in half-metallic transition metal oxides - Huang, D. J.; Tjeng, L. H.; Chen, J.; Chang, C. F.; Wu, W. P.; Rata, A. D.; Hibma, T.; Chung, S. C.; Shyu, S.-G.; Wu, C.-C.; Chen, C. T.; Huang, DJ; Tjeng LH; Chen J; Chang CF; Wu WP; Rata AD; Hibma T; Chung SC; Shyu SG; Wu CC; Chen CT (Surface Review and Letters, 2002)
Spin-resolved photoemission and absorption studies of Fe 3 O 4 and CrO 2 epitaxial thin films have been reviewed to address the relationship between the electron correlation effects and the half-metallic properties of these two materials. Spin-resolved photoemission results suggest that Fe 3 O 4 should be considered as a strongly correlated system, and that Fe 3 O 4 is not a half-metal. Spin-resolved O 1s X-ray absorption measurements on ferromagnetic CrO 2 reveal that the spin polarization of the unoccupied states closest to the Fermi level approaches 100%, confirming the half-metallic ferromagnetic nature of the material. The spin polarization of the main line of the unoccupied states, on the other hand, is found to be only 50%, indicating a very atomic-like behavior of the Cr 3d2 ions.